2010
DOI: 10.1007/s13337-011-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Tomato leaf curl Palampur virus and Pepper leaf curl betasatellite Naturally Infecting Pumpkin (Cucurbita moschata) in India

Abstract: Pumpkin cultivation in India is affected by severe incidence of a yellow vein mosaic disease. Tomato leaf curl New Delhi virus and Squash leaf curl China virus are known to be associated with this disease in India. We were able to identify a third begomovirus-Tomato leaf curl Palampur virus (ToLCPMV), from pumpkin showing typical symptoms of the disease at Varanasi based on the sequence of complete DNA-A genome of the virus. The complete DNA-A sequence of the virus shared more than 99% sequence identity with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Similarly, previous report showed that trans-replication of betasatellites in plants inoculated with TYLCCV and TbCSV has been well proved through agro-inoculation [50]. Further, yellow vein mosaic disease of pumpkin was caused by Tomato leaf curl Palampur virus, is associated with Pepper leaf curl betasatellite [51], and in cotton, single betasatellite molecule will support for pathogenicity of multiple viruses [10].…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, previous report showed that trans-replication of betasatellites in plants inoculated with TYLCCV and TbCSV has been well proved through agro-inoculation [50]. Further, yellow vein mosaic disease of pumpkin was caused by Tomato leaf curl Palampur virus, is associated with Pepper leaf curl betasatellite [51], and in cotton, single betasatellite molecule will support for pathogenicity of multiple viruses [10].…”
Section: Discussionmentioning
confidence: 59%
“…As compared to ToLCNDV, the ToLCPMV is a recently identified begomovirus, reported from bitter cucumber, Rumex sp, tomato, pumpkin, squash, cucumber, bitter gourd, common bean, water melon, chilies, and muskmelon from India and Iran (Namrata et al 2010;Heydarnejad et al 2009;Esmaeili et al 2015). In Pakistan ToLCPMV was first detected in 2007 infecting Bitter gourd (Momordica charantia L.), showing typical symptoms of the disease including chlorosis, leaf crumpling, vein thickening, and stunting of plants (Ali et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The common viruses involved in the yellow mosaic infection of cucurbits are Cucumber green mottle mosaic virus (CGMMV), Zucchini yellow mosaic virus (ZYMV), Watermelon mosaic virus (WMV), Papaya ring spot virus (PRSV) and Squash leaf curl China virus (SLCCNV) (Ali et al 2004;Tahir et al 2010). Tomato leaf curl Palampur virus (ToLCPMV) has been investigated as an infectious agent of leaf curl disease in cucurbits, tomato, cucumber and muskmelon (Namrata et al 2010;Heydarnejad et al 2009;Esmaeili et al 2015;Malik et al 2011). This virus is relatively new introduction in agro ecological zone of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The specific begomoviruses that are prevalent in the disease hot spot we have used in this study are unknown or were not determined in Tomato lines (F 6 ) derived from FLA478-6-1-11 9 CLN1621E this study. However, it is likely that the population of begomoviruses include both monopartite and bipartite begomoviruses (Chakraborty et al 2003;Namrata et al 2010;Venkataravanappa et al 2014). The two virus isolates used in the present study represent begomovirus species that are predominant in India (Tiwari et al 2010;Jyothsna et al 2013).…”
Section: Discussionmentioning
confidence: 99%